WHITE BANK, BLACK MONEY BRAZILIAN GEOPOLITICAL OF THE BRAZILIAN DEVELOPMENT BANK TO FINANCING ODEBRECHT IN ANGOLA - Goes, Fernanda Lira (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
Living in a racial segregated country, I understand the premise to enlarge and to deepen those debates about inequalities resulted of racial prejudice and discrimination. This paper theme is a proposition to criticize territory of money as consequence of Brazilian geopolitical intervention thru public bank fomentation to large companies interested in accumulation of capital. The objective presupposes to analyses relations of power linked to Brazilian geopolitical of the Brazilian Development Bank (BNDES) financing to Odebrecht in Angola.